A Foreign Aid and Economics Development Nexus: The Case of Sierra Leone: Foreign Aid in Sierra Leone, Economic Development in Sierra Leone, - Duramany-Lakkoh, Ezekiel Kalvin (Archives of Business Research, 2021)
This study investigates the impact of foreign aid on economic growth in Sierra Leone using cointegration and error correction methodology by Johansen and Juselius (1990). Utilizing secondary data for the period 1970 to 2018, the empirical estimation revealed that foreign aid in Sierra Lone is positively and significantly related to economic growth both in the short run and long run, confirming the importance of the study. The policy implication of the study is that the Sierra Leone government should seek more foreign aid to accelerate economic growth and development.